SELECTION OF LEAF AND SPICY AROMATIC AGRICULTURAL CROPS: STATUS AND DIRECTIONS - A. V. Soldatenko; V. F. Pivovarov; V. A. Kharchenko; M. I. Ivanova (Овощи России, 2019)
The aim of the present work was evaluation of the current state and leading directions in selection of leaf and spicy-aromatic vegetables crops belonging to the Asteraceae, Apiaceae, Brassicaceae, Lamiaceae, Chenopodiaceae families. Analysis of leaf and spicy aromatic plant production revealed that at present time these crops become more and more popular. Being a source of essential to human organism vitamins, antioxidants and biologically active compounds they enrich food with marvelous taste and aroma. The main directions in the selection of these crops and presented database of leaf and spicy-aromatic crops genebank promote the selection process optimization. Modern varieties of leaf and spicy-aromatic crops of Federal Scientific Vegetable Center selection are considered to be competitive and promising for import substitution.